Targeting programmed cell death in diabetic kidney disease: from molecular mechanisms to pharmacotherapy - Fengzhao Liu; Zhenyu Yang; Jixin Li; Tao Wu; Xiangyu Li; Lijuan Zhao; Wenru Wang; Wenfei Yu; Guangheng Zhang; Yunsheng Xu (Molecular Medicine)
Abstract Diabetic kidney disease (DKD), one of the most prevalent microvascular complications of diabetes, arises from dysregulated glucose and lipid metabolism induced by hyperglycemia, resulting in the deterioration of renal cells such as podocytes and tubular epithelial cells. Programmed cell death (PCD), comprising apoptosis, autophagy, ferroptosis, pyroptosis, and necroptosis, represents a spectrum of cell demise processes intricately governed by genetic mechanisms in vivo. Under physiological conditions, PCD facilitates the turnover of cellular populations and serves as a protective mechanism to eliminate impaired podocytes or tubular epithelial cells, thereby preserving renal tissue homeostasis amidst hyperglycemic stress. However, existing research predominantly elucidates individual modes of cell death, neglecting the intricate interplay and mutual modulation observed among various forms of PCD. In this comprehensive review, we delineate the diverse regulatory mechanisms governing PCD and elucidate the intricate crosstalk dynamics among distinct PCD pathways. Furthermore, we review recent advancements in understanding the pathogenesis of PCD and explore their implications in DKD. Additionally, we explore the potential of natural products derived primarily from botanical sources as therapeutic agents, highlighting their multifaceted effects on modulating PCD crosstalk, thereby proposing novel strategies for DKD treatment.